2015
DOI: 10.13065/jksdh.2015.15.05.889
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life (OHIP-14) according to smoking

Abstract: Objectives:The purpose of the study is to investigate the oral health-related quality of life according to smoking in the male workers in Gunsan. Methods: A self-reported questionnaire was completed by 460 male workers in Gunsan from April 13 to 30, 2015. Among 460 workers, smokers were 205 and nonsmokers were 255. The questionnaire included three questions of general characteristics of the subjects, four questions of subjective oral health, fourteen questions of OHIP, ten questions of sobriety test (AUDIT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Later on, a shortened OHIP-14 was derived from the OHIP-49 by using two items for each domain [ 8 ]. Korean version of the OHIP and its short-form OHIP-14K were developed in 2007 [ 9 ], and has been applied in various geriatric researches for Koreans [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, a shortened OHIP-14 was derived from the OHIP-49 by using two items for each domain [ 8 ]. Korean version of the OHIP and its short-form OHIP-14K were developed in 2007 [ 9 ], and has been applied in various geriatric researches for Koreans [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Younger elders [ 15 , 17 ], females [ 17 , 18 ], and lower education [ 19 , 20 ] were associated with poor OHRQoL. Smoking [ 10 ], alcohol consumption [ 10 , 20 ] also had a negative impact on OHRQoL. Moreover, many studies indicated that general health problems (metabolic syndrome [ 21 , 22 ], frailty [ 23 ]), and periodontitis [ 24 ] were associated with poor QoL.…”
Section: Introductionmentioning
confidence: 99%